2016
DOI: 10.1038/srep27121
|View full text |Cite
|
Sign up to set email alerts
|

Acousto-microfluidics for screening of ssDNA aptamer

Abstract: We demonstrate a new screening method for obtaining a prostate-specific antigen (PSA) binding aptamer based on an acoustofluidic separation (acoustophoreis) technique. Since acoustophoresis provides simultaneous washing and separation in a continuous flow mode, we efficiently obtained a PSA binding aptamer that shows high affinity without any additional washing step, which is necessary in other screening methods. In addition, next-generation sequencing (NGS) was applied to accelerate the identification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…More recently, several modified microfluidic techniques have been established to enhance the efficiency in selecting aptamers, including Capillary Electrophoresis (CE) microfluidic SELEX [ 26 ], bead-based microfluidic SELEX [ 27 , 28 ] and protein microarray-microfluidic chip SELEX [ 29 ].…”
Section: Limitations and Advancements In Aptamer Selectionmentioning
confidence: 99%
“…More recently, several modified microfluidic techniques have been established to enhance the efficiency in selecting aptamers, including Capillary Electrophoresis (CE) microfluidic SELEX [ 26 ], bead-based microfluidic SELEX [ 27 , 28 ] and protein microarray-microfluidic chip SELEX [ 29 ].…”
Section: Limitations and Advancements In Aptamer Selectionmentioning
confidence: 99%
“…While for virus manipulation, Ness et al [43] demonstrate extraction and enrichment of MS2 virus from human nasopharyngeal samples by integration of acoustic force to remove host cells, debris, and pollen from the sample and later with electric field force to attract the virus, which is a negatively charged species, and to migrate from sample to co-flowing buffer. Further, Park et al [44] perform washing and screening of prostate-specific antigen (PSA)-binding aptamer, a single-stranded DNA (ssDNA), using an acoustophoretic separation. The ssDNA pool comprising of ssDNA library is incubated with microbeads which modified with target molecule, before it is introduced to acoustophoretic separation device, where the microbeads with target-bound DNA fragments are focused on central buffer due to acoustophoretic force, while unbound protein and ssDNA are remained in the original buffer at the side flow.…”
Section: Acoustophoretic Manipulation Of Bioparticlesmentioning
confidence: 99%
“…Augustsson et al reported a microfluidic device to separate phages using antigen (grass pollen allergen; Phl p5)-coated microbeads from commonly used phage display libraries. Park et al developed an acoustofluidic device as a new screening method using a prostate-specific antigen (PSA)-coated microbeads for selection of aptamer based on an acoustofluidic separation (acoustophoresis) technique [28]. In addition, Shields et al demonstrated a new acoustofluidic sorting method using elastomeric affinity particles in order to capture and transport cells into antinode (general channel wall) of an acoustic standing wave [29].…”
Section: Introductionmentioning
confidence: 99%